Total flavone extract from Ampelopsis megalophylla induces apoptosis in the MCF-7 cell line - Gui, Chun (Int J Oncol, 2021)
Ampelopsis megalophylla has been found to demonstrate anticancer activities in human cancer cells; however, the effect of total flavone extract (TFE), commonly used in Traditional Chinese Medicine, remains unclear. Furthermore, there is limited information on its effects on breast cancer cell lines. The present study aimed to investigate the inhibitory effects of TFE in different human cancer cell lines. In addition, the underlying mechanisms and the signaling pathways involved were also investigated by determining tumor cell morphological changes, and differences in the cell cycle, apoptosis, mitochondrial transmembrane potential, and related protein expression levels in a breast cancer cell line. It was found that TFE inhibited proliferation in seven cancer cell lines (HeLa, A549, MCF-7, HepG2, A2780, SW620 and MDA-MB-231 and demonstrated a strong inhibitory effect on MCF-7 cell proliferation. Cell morphological changes were also observed and arrested at the G(2)/M phase following treatment with TFE at different concentrations. In addition, TFE disrupted the mitochondrial membrane potential and upregulated the expression level of apoptotic proteins, including caspase-3, -8 and -9, the Bax/Bcl-2 ratio, and Apaf-1 in time-dependent manner. These results indicated that TFE induced apoptosis of the MCF-7 cells via a mitochondrial-mediated apoptotic pathway. In conclusion, TFE is potentially effective in treating breast cancer.